2001
DOI: 10.4049/jimmunol.167.5.2902
|View full text |Cite
|
Sign up to set email alerts
|

Bystander Activation Involving T Lymphocytes in Herpetic Stromal Keratitis

Abstract: Herpes simplex virus infection of mouse corneas can lead to the development of an immunopathological lesion, termed herpetic stromal keratitis (HSK). Such lesions also occur in TCR-transgenic mice backcrossed to SCID (TgSCID) that are unable to mount detectable HSV-specific immune responses. The present study demonstrates that lesion expression in such mice depends on continuous viral replication, whereas in immunocompetent mice, lesions occurred even if virus replication was terminated at 4 days after infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 25 publications
3
69
0
Order By: Relevance
“…Intralesional accumulation of activated nonspecific T cells, referred to as bystander T cells, has been reported in other localized viral infections of the brain in mouse models (37)(38)(39). With regard to HSV-1, the immunopathogenicity of corneal tissue-infiltrating bystander T cells has been shown in the mouse model of herpetic stromal keratitis (40,41). It was postulated that HSV-1 infection of the cornea induced a local environment in which expressed cytokines and chemokines attract and activate cornea-infiltrating T cells directly, rather than by TCR-mediated signaling (41).…”
Section: Discussionmentioning
confidence: 99%
“…Intralesional accumulation of activated nonspecific T cells, referred to as bystander T cells, has been reported in other localized viral infections of the brain in mouse models (37)(38)(39). With regard to HSV-1, the immunopathogenicity of corneal tissue-infiltrating bystander T cells has been shown in the mouse model of herpetic stromal keratitis (40,41). It was postulated that HSV-1 infection of the cornea induced a local environment in which expressed cytokines and chemokines attract and activate cornea-infiltrating T cells directly, rather than by TCR-mediated signaling (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that chronic parasitic infection (Leishmania donovani), associated with a strong inflammatory response, induces expansion of heterologous CD4 1 memory T cells [6]. In a model of herpetic stromal keratitis, a chronic inflammatory reaction in the corneal stroma, which follows ocular infection with herpes simplex virus, a nonantigen-specific bystander activation of CD4 1 T cells appears to account for the immunopathological lesions [7,8]. Information in human subjects is even more limited, although anecdotal observations of parallel expansions of CD4 1 T cells against tetanus toxoid (TT) during infection with influenza virus have been reported previously [9].…”
Section: Introductionmentioning
confidence: 99%
“…In corneas of BALB/c mice infected with the RE strain of HSV-1, Russell et al (2) showed that HSK resulted from CD4 ϩ T cells secreting IFN-␥, IL-12, and other lymphokines typically produced by Th1 cells. Deshpande et al (3,4) showed that activated CD4 ϩ T cells were required for the development of HSK, which occurred as a non-TCR-mediated event. On the basis of these studies, the authors proposed a bystander activation model of HSK.…”
Section: Blocking 4-1bb/4-1bb Ligand Interactions Prevents Herpeticmentioning
confidence: 99%